Illnesses and Diseases: Article or Not? That's Question! - Marta Kadorova; Zuzana Ondrackova (Communications - Scientific letters of the University of Zilina, 2005)
The paper analyses the use of articles with the names of illnesses, diseases and disorders in the English language. The paper is divided into three parts. The first one summarizes rules about the articles and illnesses in prescriptive grammar books. The second one contains a table which aims to present the list of illnesses, diseases and disorders with corresponding articles. The final one focuses on the results of the research which was based on the comparison of the theoretical background and the actual use of articles with the names of illnesses, diseases and disorders in The Family Medical Reference Book.